FDXR drives primary and endocrine-resistant tumor cell growth in ER+ breast cancer via CPT1A-mediated fatty acid oxidation - Yan, Chaojun; Gao, Ronghui; Gao, Chuan; Hong, Kai; Cheng, Meng; Liu, Xiaojing; Zhang, Qing; Zhang, Jing (Frontiers in Oncology, 2023)
The majority of breast cancers (BCs) expressing estrogen receptor (ER) have shown endocrine resistance. Our previous study demonstrated that ferredoxin reductase (FDXR) promoted mitochondrial function and ER+ breast tumorigenesis. Here, integrative analyses with targeted metabolomics assays and gene expression profiling showed that FDXR potentiated fatty acid oxidation (FAO) through positive regulation of carnitine palmitoyltransferase 1A (CPT1A) expression. Treatment with an ER antagonist (tamoxifen) or degrader (fulvestrant) increased the expression of FDXR and CPT1A. In line with this finding, we found that the FDXR-CPT1A-FAO axis was required for primary and endocrine-resistant breast cancer cell growth. Therapeutically, combining endocrine therapy with FAO inhibitors synergistically reduced primary and endocrine-resistant breast cancer cell growth, thus providing a potential combinatory treatment for ER+ breast cancer.